Comparative Analysis Of Financial Performance Of Transportation And Hospitality Sector Companies Before And During The Covid-19 Pandemic - Mutia Dea Haruya; Kartini Kartini (Ridwan Institute, 2023)
This study aims to look at differences in the financial performance of companies in the transportation and hotel sectors before and during the Covid-19 pandemic in Indonesia. This research is a quantitative study using a sample of 35 companies in the transportation and hotel sector listed on the Indonesia Stock Exchange. The data used is secondary data obtained from annual reports for the period 2018-2019 before the Covid-19 pandemic and 2020-2021 when the Covid-19 pandemic occurred. The analytical method used is a differential test using the Wilcoxon Signed Rank Test on the ROA, CR, DER, and PER variables. The results of this research show that there is a significant difference in the ROA and CR variables, where the ROA and CR values before the Covid-19 pandemic were higher than during the Covid-19 pandemic, while the value of the DER variable before the Covid-19 pandemic was not lower than during the Covid-19 pandemic period and the PER value before the Covid-19 pandemic was not higher than during the Covid-19 pandemic period in Indonesia.